Partus Prematurus Imminens Akibat Penggunaan Obat Uretonika Dosis Tinggi: Sebuah Laporan Kasus - Pratiwi, Aulia Sari; Graharti, Risti; Kusumaningtyas, Intan (Medula, 2026)
Imminent preterm labor is an obstetric condition characterized by uterine contractions accompanied by cervical changes before 37 weeks of gestation, which can lead to preterm delivery. This condition remains the leading cause of perinatal morbidity and mortality in Indonesia. According to the 2018 Basic Health Research (Riskesdas), the prevalence of premature births reached 29.5 per 1,000 live births and contributed to 35% of neonatal deaths. This study aims to report and analyze cases of imminent premature labor due to the use of high-dose urethronics, as well as to review the latest evidence-based management. Data were obtained through anamnesis, physical examination, and review of patient medical records, which were then supplemented with a literature review related to the mechanism of action of uterotonic drugs, the role of prostaglandins, and management guidelines from the WHO, ACOG, and WAPM-PMF. The results of the report showed that patients experienced active uterine contractions with premature rupture of membranes at 29–30 weeks of gestation after repeated consumption of high doses of misoprostol. The use of uretonic drugs caused an increase in contractions due to excessive prostaglandin stimulation. Management included the administration of antenatal corticosteroids to accelerate fetal lung maturation, short-term tocolytics to delay labor, and magnesium sulfate as a neuroprotective agent. It is concluded that the use of uterotonic drugs without medical supervision can be a factor in triggering imminent premature labor. A comprehensive and evidence-based management approach can reduce the risk of neonatal complications and improve pregnancy outcomes, making strict supervision and patient education important steps in preventing similar cases in the future.